2019
DOI: 10.1007/s12560-019-09408-x
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Activities of Hibiscus sabdariffa L. Tea Extract Against Human Influenza A Virus Rely Largely on Acidic pH but Partially on a Low-pH-Independent Mechanism

Abstract: Influenza A virus (IAV) infection is perennially one of the leading causes of death worldwide. Effective therapy and vaccination are needed to control viral expansion. However, current anti-IAV drugs risk inducing drug-resistant virus emergence. Although intranasal administration of whole inactivated virus vaccine can induce efficient protective immunity, formalin and β-propiolactone are the currently used and harmful inactivating agents. Here, we analyzed the antiviral activity of hibiscus (Hibiscus sabdariff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 35 publications
(47 reference statements)
0
19
0
Order By: Relevance
“…Madin–Darby canine kidney (MDCK) cells were kindly provided by H. Nagano (Hokkaido Institute of Public Health, Sapporo, Japan). The composition of MDCK cell growth medium and IAV growth medium were as previously described [ 18 ]. FCV (F9 strain) and Crandell-Rees feline kidney (CRFK) cells were kindly provided by Dr. K. Maeda (Yamaguchi University, Yamaguchi, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Madin–Darby canine kidney (MDCK) cells were kindly provided by H. Nagano (Hokkaido Institute of Public Health, Sapporo, Japan). The composition of MDCK cell growth medium and IAV growth medium were as previously described [ 18 ]. FCV (F9 strain) and Crandell-Rees feline kidney (CRFK) cells were kindly provided by Dr. K. Maeda (Yamaguchi University, Yamaguchi, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Several PDFGS interfered with IAV entry into host cells ( Table 4 ). PDFGS such as edible bird nest (EBN) extracts, lectin-like compounds from Japanese plum, green tea, guava tea, isorhamnetin, tannins, HS, and polysaccharides from marine algae suppressed IAV-host cellular interactions through the inhibition of viral HA activities ( 41 , 45 , 51 , 57 , 66 , 67 ). PDFGS such as Portulaca oleracea (P. oleracea) extracts, quercetin and EBN are able to prevent virus-host interaction by binding with strong affinity to the surface coats of IAV ( 25 , 57 , 70 ).…”
Section: Resultsmentioning
confidence: 99%
“…HS, despite having an in vitro anti-IAV activity, in vivo studies showed that the aqueous extract of HS (8 mg), neither improved survival nor reduce virus titer in PR8 infected mice ( 45 ). Furthermore, the evidence they presented suggested that the observed in vitro anti-IAV activity of HS was due to the acidic nature of HS extract ( 45 ). In a separate experiment where they vaccinated mice with IAV inactivated by acidic HS, they observed an improvement in survival rate following subsequent IAV challenge.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations